Generalized Hyers-Ulam-Rassisa Stability of An Additive (Î²1,Î²2)-Functional Inequalities With n- Variables In Complex Banach Space - an, ly van (Global Journal of Mathematical Analysis, 2022)
In this paper we study to solve the o f additive (Î²1,Î²2)-f unctional inequality with nâˆ’variables and their Hyers-Ulam stability. First are investigated in complex Banach spaces with a fixed point method and last are investigated in complex Banach spaces with a direct method. I will show that the solutions of the additive (Î²1,Î²2)-f unctional inequality are additive mapping. Then Hyersâˆ’Ulam stability o f these equation are given and proven. T hese are the main results o f this paper .